Research on depression in adolescents in Peru: a systematic review - Navarro-Loli, Jhonatan Steeven (2017)
Depression in adolescents is a multicausal phenomenon and a predictor of social problems and other disorders. Thus, it is considered a public health problem. This investigation aims to systematically review the characteristics of the scientific articles about depression in Peruvian adolescents published in Peruvian and non-Peruvian journals. The search was performed in the databases of SciELO, Latindex, Redalyc, Scopus, PubMed, and through Google, using a combination of keywords related to the construct, the sample and its origin. The unit of analysis consisted of 21 articles. The reviewed articles showed inconsistency in the reporting and bibliographic support of the research designs, sampling procedures, psychometric properties of the instruments, instruments used to assess the construct which were not evaluated in our context, and cut-off points obtained in other countries’ samples. Therefore, we can state that the reviewed articles do not fully comply with the publication standards proposed by the American Psychological Association. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.04